6ER-032 How can Dutch university hospitals contribute to affordable medicines and cost containment of total hospital drug expenditure: a Delphi study. Issue 1 (23rd March 2023) - Dane, A; Ramlal, A; Overgaag-van Hemert, M; Roos, P; Post, C; Uyl-de Groot, C; Van Der Kuy, H
Abstract : Background and Importance: Increasing expenditure on pharmaceuticals is of growing concern to the affordability of healthcare systems across Europe. As stated in the European Commission (EC)'s Pharmaceutical Strategy for Europe all stakeholders should be involved in tackling this problem. The EC has indicated that solutions along the entire drug life cycle (DLC) should be considered as it offers a more comprehensive and integrated view to address this topic. Being a stakeholder, university hospitals (UH) are engaged in multiple phases of the DLC, consisting of (pre-)clinical research, market authorisation, pricing and reimbursement, manufacturing, procurement, prescribing, dispensing and monitoring real-world effectiveness. Aim and Objectives: We aimed to explore which activities UHs perform or should perform to contribute to cost containment of medicines. Material and Methods: We used a Delphi technique and assembled an expert panel of 31 pharmaceutical experts of Dutch UHs (i.e., doctors, researchers, hospital pharmacists, directors), health insurers and governmental authorities. In the first round, we explored activities UHs currently perform or should perform throughout the DLC and what barriers or dilemmas they encounter. In the second round, we asked our panel on a 5-point Likert point scale to (dis)agree with all mentioned activities and barriers. The third round was used to reach consensus on activities and barriers which were (dis)agreed upon less than 50%. Results: The panel agreed that, considering (pre-)clinical research, UHs should increase involvement in drug repurposing and monitoring of real-world effectiveness of medicines. Furthermore, while prescribing medicines is reserved for medical specialists UHs should raise more awareness on cost-effective prescribing by doctors via more active involvement of hospital pharmacists, adjustment of national prescribing guidelines and extending pharmacotherapy education. Finally, cost containment could be enhanced by reducing spillage, e.g., efficient dosing. Controversy among the panel remained on the notion of UHs building more knowledge on regulatory affairs for marketing authorisation and increasing their effort on self-manufacturing of medicines. Agreed upon barriers restricting UHs to expand their activities were insufficient financial resources and legal and entrepreneurial expertise. Conclusion and Relevance: UHs should increase their efforts to reduce costs of medicines throughout the whole DLC, but especially on activities regarding drug repurposing, avoidance of spillage and cost-effective prescribing. References and/or Acknowledgements: Conflict of Interest: No conflict of interest.